Preliminary screening of cytotoxic properties of Baccaurea angulata in several human cancer cell lines in vitro - Abdull Rasad, Mohammad Syaiful Bahari (2013)
Fruits have been acknowledged as a reservoir for numerous bioactive compounds. Baccaurea angulata, belonging to the Euphorbiaceae family, has been reported to contain several nutritional properties such as proteins and carbohydrates. Presently, B. angulata has not been fully exploited as little is known regarding its scientific properties. This preliminary study aims to explore the cytotoxicity effects of various extracts and fibers of B. angulata on human cancer cells. Cytotoxicity effects of B. angulata were evaluated on cervix cancer (HeLa) and skin melanoma (A375) cells through treatment with hexane, methanol and dichloromethane extracts of B. angulata as well as with novel B. angulata fibers (whole fruit and berries) via direct contact method. The growth inhibitions of the samples were evaluated through Methylene Blue Assay (MBA), with incubation time of 24, 48 and 72 hours. From the results, it was observed that for HeLa cells, berries showed the highest growth inhibition (90.69 μg/mL, 72 hours). The solvent-based extracts were found to be cytotoxic towards HeLa cells with methanol extracts exhibiting the highest cytotoxicity with EC50 of 17.21 μg/mL. For A375 cells, all extracts also exhibited cytotoxic effects, where the highest inhibition activity was induced by hexane extracts (89.40 μg/mL, 72 hours). Consequently, the study indicates that B. angulata fruit may have significant growth inhibitory and cytotoxicity effects toward HeLa and A375 cells. It can be presumed that B. angulata fruit has the potential to be used as a new alternative resource that could be fundamental in future endeavors for prospective therapeutic treatments for cancer.